Europe’s Green Deal: Is the Middle Class Left Behind? - LaBelle, Michael; Szép, Tekla (Journal of Public Governance, 2022)
Objective: In this paper, we fundamentally question the Fit for 55 starting assumption that reducing household energy consumption is beneficial or even neutral (i.e. not detrimental) for households in all Member States in the short period up to 2030. This article identifies the plight of households unable to improve their well-being without increasing the consumption of fossil fuels. Tackling energy poverty and addressing social inequality issues is a cornerstone. Around 35 million people live in energy poverty in the European Union (European Commission, 2023), and tens of millions more are at high risk of energy poverty. However, ensuring the well-being of EU citizens requires a broader awareness of the implications of reducing fossil fuel use. Research Design and Methods: The research methodology relies on a range of quantitative methods: Gini coefficient, Hoover index, Decomposition adjusted Hoover index, rank correlation coefficient, path analysis, and decoupling factors are presented. We also analyze from different perspectives highlighting inequalities and the direct and indirect relationship between residential energy use and HDI and decoupling. Findings: Based on projected policy impacts, consumers will need to pay more for using fossil fuels. Higher energy taxes will likely impact middle-class families who are not the EU’s Climate Fund targets. Based on our previous projections, at least the bottom two-thirds of the middle class (which roughly represents the 2nd, 3rd, and 4th quintiles) also need support. There is a risk that in countries where HDI and per capita household energy use are still tightly connected, the growth in household energy use (driven mainly by higher incomes and increasing human welfare) will be strongly constrained by higher energy costs. In the EU energy convergence will slow down, or even stop, so that the current spatial disparities in HDI and in residential energy use will persist. Implications: Decreasing the differences in HDI and residential energy use is necessary to achieve social and economic convergence and reduce the inequalities in living standards across the EU Member States. Changes in household energy use in the EU have both direct and indirect impacts on HDI; any increase or decrease in energy use will be immediately reflected in human well-being. Contribution/Value Added: This article highlighted those countries most exposed to a reduction in well-being. Member States below the saturation point are at a much higher risk of negative impacts of residential energy use on human development. Tackling energy poverty is a very important issue, but in this case, at least the bottom two-thirds of the middle class (which roughly represents the 2nd, 3rd, 4th quintiles) also need support. This could include preferential loans, grants, and technical assistance to enable them to make the necessary energy efficiency improvements and deep renovations that will bring real energy savings.